The role of galectins in mediating the adhesion of circulating cells to vascular endothelium - Souchak, Joseph; Mohammed, Norhan B. B.; Lau, Lee Seng; Dimitroff, Charles J. (Frontiers in Immunology, 2024)
Vascular cell adhesion is a complex orchestration of events that commonly feature lectin–ligand interactions between circulating cells, such as immune, stem, and tumor cells, and endothelial cells (ECs) lining post-capillary venules. Characteristically, circulating cell adherence to the vasculature endothelium is initiated through interactions between surface sialo-fucosylated glycoprotein ligands and lectins, specifically platelet (P)- or endothelial (E)-selectin on ECs or between leukocyte (L)-selectin on circulating leukocytes and L-selectin ligands on ECs, culminating in circulating cell extravasation. This lectin–ligand interplay enables the migration of immune cells into specific tissue sites to help maintain effective immunosurveillance and inflammation control, the homing of stem cells to bone marrow or tissues in need of repair, and, unfortunately, in some cases, the dissemination of circulating tumor cells (CTCs) to distant metastatic sites. Interestingly, there is a growing body of evidence showing that the family of β-galactoside-binding lectins, known as galectins, can also play pivotal roles in the adhesion of circulating cells to the vascular endothelium. In this review, we present contemporary knowledge on the significant roles of host- and/or tumor-derived galectin (Gal)-3, -8, and -9 in facilitating the adhesion of circulating cells to the vascular endothelium either directly by acting as bridging molecules or indirectly by triggering signaling pathways to express adhesion molecules on ECs. We also explore strategies for interfering with galectin-mediated adhesion to attenuate inflammation or hinder the metastatic seeding of CTCs, which are often rich in galectins and/or their glycan ligands.